Electronic Principles, Experiments Manual - Paul Malvino Albert (Mc Graw Hill, 1999)
The book is written by one of the most respected authors in the electronics field. Electronic Principles offers the clearest, most complete coverage for use in courses on Electronic Principles, Electronic Devices, Linear Electronics, and Electronic Circuits. The new edition retains Malvino's clear writing style and is supported throughout with abundant examples and hundreds of clear illustrations. This edition has a new full-color design format. Colorful illustrations make electronic components in circuit diagrams more easily follow and understand the circuitry. There is a consistent use of color to various components. This edition has been updated to keep coverage in step with the fast-changing world of electronics. This edition also introduces CATS (Computer-Aided Tutorial Software), a CD-ROM packaged with the text that contains practice exercises for applying the text's theories